The Aged Poor of Massachusetts - Young, Allyn A. (Quarterly Journal of Economics, 1926)
Journal Article The Aged Poor of Massachusetts Get access Allyn A. Young Allyn A. Young Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 40, Issue 3, May 1926, Pages 549–554, https://doi.org/10.2307/1885178 Published: 01 May 1926